METHOD OF PROCESSING THE REFLECTED SIGNALS FROM PULSED EDDY CURRENT CONVERTERS - Abramovych, A. A.; Kashirsky, I. S.; Poddubny, V. A. (Radio Electronics, Computer Science, Control, 2018)
Context. The problem of processing signals of eddy current converters (ECC) reflected from metal inhomogeneities in a dielectric medium (soil) is considered. The object of the study was the method of processing reflected signals. Objective. The purpose of the work is to create a method of digital signal processing that is convenient for digital processing, which allows to expand the capabilities of an ECC by analyzing the type of metal in a subset of nonmagnetic (copper, gold, silver, etc.) and magnetic (steel, nickel) materials. Method. The method of processing reflected from metal inhomogeneities signals of eddy current converters in the time domain is proposed, which allows to identify the type of metal within a subset of non-magnetic and magnetic materials, which makes it possible to increase the detection efficiency of objects made of non-ferrous and precious metals hidden in a dielectric medium. The time signal obtained by the ECC is digitized and converted into a graphic image by the software, in which the continuous signal change is replaced by the characteristic lines (graphically). Graphic images have a high information saturation, because their characteristic lines differ in coordinates, height and polarity. The crossing points of the signal through zero are also fixed. This form of signal is clear and convenient for comparing signals. Results. The proposed method is implemented programmatically and experimentally confirmed the possibility of its use for solving the problem of identifying the type of metal within the subset of non-magnetic and magnetic materials. Conclusions. The conducted experimental researches have confirmed the efficiency of the proposed method for processing signals of eddy current converters and the software of its implementer. They allow us to recommend a method for solving the problems of identifying the metal from which the object is made, which is located in a dielectric medium (soil). Prospects for further research are the adaptation of mathematical and software to identify the signals of the serial eddy current transducers, which will expand their functionality.